ANALISIS KERUSAKAN JALAN DENGAN METODE PCIDAN BINA MARGA JALAN NAGARI KOTO KACIAK KABUPATEN PASAMAN - Kartika Sari, Dian; Yermadona, Helga; Dewi, Selpa (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2023)
Roads are land transportation infrastructure that has a very important role in the land transportation sector that supports the continuity of the distribution of goods and services to encourage economic growth in an area. Good road conditions will facilitate community activities, if there is road damage, community activities will be hindered so that accidents can occur. The purpose of this study was to determine the types of damage and the pavement index value for Nagari Koto Kaciak road, Pasaman Regency, so that it could compare the value of the condition of the Nagari Koto Kaciak road, Pasaman Regency based on two predetermined methods. The method used is the PCI (Pavement Condition Index) method and the Bina Marga method. Assessment of road conditions in the PCI method is ranked from 0-100 while the Bina Marga method is based on the order of road priority with a value range of 0-7. Types of damage found on Nagari Koto Kaciak road, Pasaman Regency along a length of 2 km, included holes, crocodile skin cracks, patches, block cracks and side cracks. In the PCI method the average value obtained is 66.31 which is a good road condition. In the Bina Marga method, the priority order value is 6, meaning that the road is under periodic maintenance. After comparing the results of the research on the condition of the Nagari Koto Kaciak road, Pasaman Regency with the two methods, it turns out that the results and values are almost the same, namely the condition of the road is still in good condition but requires maintenance so as not to worsen road conditions.